Survey Based on Security Aware Caching Scheme for IoT Based Information Centric Networking - Sakthivanitha, M.; Saradha, S. (EAI Endorsed Transactions on Energy Web, 2020)
Information-Centric Networking (ICN) empowered by information-centric paradigm takes popular paradigm place of host-centric networking of communication networks, which in turn helps prioritizing the labeled content delivery, with no information on the origin of the contents. Security of client and content, originating place, and identity privacy are inherent in ICN paradigm design in contrast to present host centric concept where they are introduced as a second-thought. But, with its genesis, the ICN paradigm exhibits different unresolved challenges in privacy and security. In this work, current literature in ICN privacy and security are explored and open challenges are presented. Especially, three extensive subjects: security threats, risks involved with privacy, access control management techniques are explored. Primary objective of ICN is to modify the present location-based IP network architecture to location-free and content-oriented network framework. ICN can satisfy the demands for caching to the neighbouring edge devices with no more storage deployed. In this work, an several architecture for effective caching at the edge devices for data-centric IoT applications and a rapid content access that depends on novel deep learning techniques and caching processes in ICN. The novel learning-oriented effective caching technique yields the solution to the problem involving the available hash and on-path caching techniques, and the newly introduced content popularity scheme improves the availability content at the devices in the vicinity for minimizing the content transfer time and packet loss ratio.